Determinan Struktur Modal Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index - Yogi Saputra; Ummu Salma Al-Azizah; Yadi Nurhayadi (LPPM ISNJ Bengkalis, 2021)
This study aimed to analyze the factors that influence the capital structure of companies listed on the Jakarta Islamic Index (JII). These factors consist of company size, return on assets (ROA), return on equity (ROE), inflation, and growth in the gross domestic product (GDP). This research is quantitative research with a purposive sampling method and obtained a sample of 9 companies. The data used is secondary data in financial reports on companies registered with JII in 2015-2019. Data analysis using the multiple linear regression method. The results showed that ROA had a significant adverse effect on the capital structure, ROE has a significant positive effect on the capital structure, firm size does not affect the capital structure, inflation does not affect the capital structure, GDP growth does not affect the capital structure. Simultaneously, firm size, ROA, ROE, inflation, and GDP growth significantly affect the capital structure.